Strategi Peningkatan Daya Saing Usaha Kecil Menengah Melalui Peningkatan Mutu Sekolah Menengah Kejuruan - Pristi, Nurkholis Abellian; Sjafri, Aida Vitayala; Suprayitno, Gendut (Institut Pertanian Bogor, 2023)
Superior human resources is one of the long-term plans built by the government to reach Indonesia's gold in 2045. The quality of human resources is strongly influenced by improving the quality of education, especially vocational education. There are at least two main challenges to improving human Resources quality, namely low labor education and skills owned by Indonesian workers that are not yet aligned with the industry. Therefore, vocational education needs to be returned to its dignity, especially at the vocational level. This study seeks to identify problems, build conceptual models and establish development strategies to solve problems. The method used with the soft system methodology, which was developed into seven stages of improvement to produce a concrete strategy based on the comparison between the real world and the conceptual model. The results of this study are the steps offered to develop VHS towards a better way to strengthen the mental of VHS students, provide full-service support to VHS graduates, strengthen school institutions, and improve the quality of school human resources. The four major points will be implemented through 16 sub-strategies, namely planting character education and industrial work culture for students, rebranding vocational schools, improving foreign language skills and digital literacy for students, providing quality internships and industry-based certification for students, building supply demand mapping, tracer study studies, strengthening BKK and job matching services, student support for entrepreneurship, alignment of vocational school ecosystems, strengthening the role of LSP P1, encouraging Tefa to be BLUD, cooperation to build an industrial class, training and development of school human resources and updating of educational teaching materials 4.0.